األرض في القراّن الكريم دراسة موضوعية تحليلية - Muthhir Mohammed Tahir Mohammed (QALAAI ZANIST SCIENTIFIC JOURNAL, 2019)
This study deals with the land in the Holy Quran, an analytical and objective study. The importance of the subject to the land in our lives stems from the importance of the Qur'an. And the nature of the study necessitated the use of the inductive and descriptive analytical method. The researcher reached a number of results, of which the earth remains an excellent laboratory for all scientists and scholars who seek the truth and those who dig in their strata will discover every new day, and whoever is corrupted in this land, Punishment Fair in the world and the Hereafter, and the succession of God in the land comes good deeds and acts of worship, and spent his life in sin no longer lived, and recommended that studies should intensify in the Earth science, because it relieves a lot of raised ground disasters.